The Effect of Informative Video to Reduce Anxiety in Patients with Third Molar Surgery - Nita Layli Hanifah; Eti Poncorini Pamungkasari; Rita Benya Adriani (Journal of Health Promotion and Behavior, 2021)
Background: Dental anxiety is one type of anxiety that provides major complications for patients and dentists. Third molar extraction is one of the most common surgical procedures in the field of oral and maxillofacial surgery which is accompanied by various anxiety triggers. Anxiety due to procedures performed during dental procedures causes anxiety 60%-80% in patients who will undergo surgery. This study aims to estimate the effect of providing informative videos on the level of anxiety in patients undergoing third molar surgery based on a number of previous primary studies.Subjects and method: This study is a systematic and meta-analysis study, with the following PICO Population: Patients 18-45 years old old, Intervention: Informative video about third molar surgery, Comparison: Without informative video, Outcome: Anxiety levels. The articles used in this study were obtained from several databases, including PubMed, Scopus, Hindawi, Proquest, ScienceDirect and Google Scholar. This article was collected for 1 month. The keywords to search for articles were as follows: "Video" OR "Audiovisual" AND "Dental Anxiety" OR "Anxiety" AND "Third Molar Surgery" AND "Randomized Controlled Trial". The articles included in this study are full text articles with a Randomized Controlled Trial study design. Articles were collected using PRISMA flow diagrams. Articles were analyzed using the Review Manager 5.3 aplikasi applicationResults: A total of 9 articles were reviewed in this meta-analysis. The study showed that informative videos have an effect on reducing anxiety. (Standardized Mean Difference= -0.05; 95% CI= -0.19 to 0.08; p= 0.44). The funnel plot indicated publication bias.Conclusion: Informative video about dental surgery reduce anxiety levels.Keywords: Informative video, dental anxiety, third molar surgeryCorrespondence: Nita Layli Hanifah, Masters Program In Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126,  Central Java. Email: Nitalaylii63@gmail.com.Journal of Health Promotion and Behavior (2021), 06(01): 80-90. https://doi.org/10.26911/thejhpb.2021.06.01.08